Thermostructural Analysis of Plate-Type Heat Exchanger Prototypes Considering Weld Properties - Kee-nam Song; Sung-deok Hong (Science and Technology of Nuclear Installations)
The mechanical properties in a weld zone are different from those in the parent material owing to their different microstructures and residual weld stresses. Welded plate-type heat exchanger prototypes made of Hastelloy-X alloy were manufactured, and performance tests on the prototypes were performed in a small-scale nitrogen gas loop at the Korea Atomic Energy Research Institute. Owing to a lack of mechanical properties in the weld zone, previous research on the strength analyses of the prototypes was performed using the parent material properties. In this study, based on the mechanical properties of Hastelloy-X alloy obtained using an instrumented indentation technique, strength analyses considering the mechanical properties in the weld zone were performed, and the analysis results were compared with previous research. As a result of the comparison, a thermostructural analysis considering the weld material properties is needed to understand the structural behavior and evaluate the structural integrity of the prototype more reliably.